Consumer’s Perception of Organic Vegetables Traceability in Jabodetabek - Izazi Haibati; Eko Ruddy Cahyadi; Elisa Anggraeni (Universitas KH. Abdul Chalim Mojokerto, 2025)
Organic vegetables are one of the choices in ensuring safe and quality food that is beneficial for health. However, efforts to ensure organic vegetables that are free from pesticides or other chemicals must still be made as an effort to improve the quality of life. The purpose of this study was to determine customer perceptions of food traceability information on organic vegetables. The method used by the researcher was a quantitative method with descriptive statistical and perceptual analysis. Data were obtained by distributing questionnaires via Google Form. The technique used in selecting respondents was convenience sampling. Perceptions of food traceability information were assessed through five variables, namely informativeness, trustworthiness, food safety, reliability, product diagnosticity. Food traceability information on organic vegetables was rated very high on the five attributes of traceability information, namely informativeness, trustworthiness, food safety, reliability and product diagnosticity. The results showed that there was a significant difference between men and women in assessing the five attributes. Female respondents tended to rate the five attributes of traceability information on organic vegetables lower than male respondents. Suggestions for further research are that the objects used can be replaced with other food products or other research areas.